ARARAS-CANINDÉS (Ara ararauna - Psittacidae) COMO HOSPEDEIRAS DE Leishmania spp. - Judson Matias de Arruda dos Santos (2024)
Leishmaniases are a group of infectious diseases that present different clinical and epidemiological manifestations and have a wide global distribution. In the New World, they are considered zoonoses, with etiological agents being protozoa of the genus Leishmania, parasites of great importance to public health in Brazil, a country endemic for all forms of the disease. Currently, mammals are considered the primary reservoirs of Leishmania spp. in the environment; however, there are few reports of contact between domestic and wild bird species with the parasite. This raises the question about the possible role of birds in the transmission cycle of leishmaniasis in nature, including in Mato Grosso do Sul. This study aimed to analyze Ara ararauna as potential hosts of Leishmania spp. in Campo Grande, Mato Grosso do Sul. A total of 47 individuals of the species Ara ararauna, both free-living and captive, were analyzed using molecular biology techniques for the detection of Leishmania DNA. In this study, there were a total of six (12.7%) specimens positive for Leishmania, of which four were pups. Of these, four were living in the wild and two were in captivity. For the first time, birds of the species Ara ararauna were reported harboring the Leishmania parasite; however, this is not not enough to state that these birds participate in the leishmaniasis transmission cycle. Further studies are needed to clarify the eco-epidemiology of leishmaniasis.